Development of a Method of Determining Organic Phosphorus Pesticides in Raw Water for Water Supply by Liquid Chromatography-Inductively Coupled Plasma Mass Spectrometry - FUKUDA, Masayuki; MIYAMOTO, Shiori; OHKURA, Toshihiro; KAGAWA, Noriko; SHINOMIYA, Hiroto; YOSHIDA, Kimi; NITTA, Yuko (Journal of Japan Society on Water Environment, 2013)
Since glyphosate is used as an herbicide all over the world and mass-produced in Japan, it has become one of the complementary items set in determining drinking water quality standards in Japan. This compound has thus far been determined using derivatization-HPLC methods, which require rather complicated analytical procedures. In the present study, to determine organic phosphorus compounds including glyphosate and its main metabolite aminomethyl phosphoric acid (AMPA), glufosinate and its main metabolite 3- (metylphosphinico) propionic acid (MPPA), and fosetyl, we have developed a simple and rapid method employing liquid chromatography-inductively coupled plasma mass spectrometry (LC/ICP/MS). These compounds were directly injected to and separated in an ion exchange column using formic acid as the solvent, and phosphorus (31P) in the fractions was measured as 31P16O+ generated by a reaction with oxygen, which enabled high-sensitivity measurements. The calibration curves for the compounds were linear within the range of 0.02-30 mg·L-1 (r>0.999). The recovery rates of the compounds from the river water and groundwater samples were higher than 91.6%, with relative standard deviations less than 3.8%, suggesting that the method described in this study is useful for a rapid and simultaneous determination of organic phosphorus pesticides.